Designing a bioremediator: mechanistic models guide cellular and molecular specialization. (April 2020) - Zaccaria, Marco; Dawson, William; Cristiglio, Viviana; Reverberi, Massimo; Ratcliff, Laura E; Nakajima, Takahito; Genovese, Luigi; Momeni, Babak
Abstract : Bioremediators are cells or non-living subcellular entities of biological origin employed to degrade target pollutants. Rational, mechanistic design can substantially improve the performance of bioremediators for applications, including waste treatment and food safety. We highlight how such improvements can be informed at the cellular level by theoretical observations especially in the context of phenotype plasticity, cell signaling, and community assembly. At the molecular level, we suggest enzyme design using techniques such as Small Angle Neutron Scattering and Density Functional Theory. To provide an example of how these techniques could be synergistically combined, we present the case-study of the interaction of the enzyme laccase with the food contaminant aflatoxin B1 . In designing bioremediators, we encourage interdisciplinary, mechanistic research to transition from an observation-oriented approach to a principle-based one.